2008
DOI: 10.1259/bjr/19492531
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of CT prediction of poor prognostic features in colonic cancer

Abstract: Whilst imaging of poor prognostic features in rectal cancers has assisted pre-operative treatment stratification, such features have yet to be evaluated in colonic cancers. This study aims to develop criteria for identifying poor prognostic features in colonic tumours and assess the accuracy of CT prediction against histopathology. Criteria were developed for predicting T-stage and N-stage, the presence of extramural vascular invasion and involvement of the retroperitoneal surgical margin (RSM). These criteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
42
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(46 citation statements)
references
References 28 publications
3
42
1
Order By: Relevance
“…Our study has the largest series in which RSM was evaluated radiologically and compared pathologically, in the literature. Similar to Burton et al (11), DA was found to be 79% in the evaluation of RSM involvement. Agreement with pathology was not very good in both studies.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Our study has the largest series in which RSM was evaluated radiologically and compared pathologically, in the literature. Similar to Burton et al (11), DA was found to be 79% in the evaluation of RSM involvement. Agreement with pathology was not very good in both studies.…”
Section: Discussionsupporting
confidence: 82%
“…In T staging, the agreement between the observers was slight in our study (ĸ=0.351) and similarly it was slight (ĸ= 0.214) in a study performed by Burton et al (11). On the other hand, in Anderson et al (16), agreement between three observers was moderate to substantial (ĸ=0.523, 0.540, and 0.712) when staging was performed on axial images.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…16 The accuracy of MRI in this study for the identification of EMVI was again good at 74% for Reader 1 and 69% for Reader 2. The accuracy of CT for the identification of EMVI is reported in three previous studies; Burton et al reported an accuracy of 55% for Observer 1 and 61% for Reader 2, 31 Dighe et al 32 reported an accuracy of 70% and Rollven et al reported an accuracy of 78% for Reader 1 and 69% for Reader 2. Rollven et al also reported the accuracy of MRI of 78% and 82%.…”
Section: Discussionmentioning
confidence: 91%